Heterozygous and homozygous variants in STX1A cause a neurodevelopmental disorder with or without epilepsy - Luppe, Johannes; Sticht, Heinrich; Lecoquierre, Francois; Goldenberg, Alice; Gorman, Kathleen M.; Molloy, Ben; Agolini, Emanuele; Novelli, Antonio; Briuglia, Silvana; Kuismin, Outi; Marcelis, Carlo; Vitobello, Antonio; et al. (European Journal of Human Genetics, 2022)
The neuronal SNARE complex drives synaptic vesicle exocytosis. Therefore, one of its core proteins syntaxin 1A (STX1A) has long been suspected to play a role in neurodevelopmental disorders. We assembled eight individuals harboring ultra rare variants in STX1A who present with a spectrum of intellectual disability, autism and epilepsy. Causative variants comprise a homozygous splice variant, three de novo missense variants and two inframe deletions of a single amino acid. We observed a phenotype mainly driven by epilepsy in the individuals with missense variants in contrast to intellectual disability and autistic behavior in individuals with single amino acid deletions and the splicing variant. In silico modeling of missense variants and single amino acid deletions show different impaired protein-protein interactions. We hypothesize the two phenotypic courses of affected individuals to be dependent on two different pathogenic mechanisms: (1) a weakened inhibitory STX1A-STXBP1 interaction due to missense variants results in an STX1A-related developmental epileptic encephalopathy and (2) a hampered SNARE complex formation due to inframe deletions causes an STX1A-related intellectual disability and autism phenotype. Our description of a STX1A-related neurodevelopmental disorder with or without epilepsy thus expands the group of rare diseases called SNAREopathies.
CRIS-Team WoS Importer:2023-01-13